2021
DOI: 10.3389/fmicb.2021.781454
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Profiling and RNA Sequencing Reveal Genome-Wide Cellular Translation and Transcription Regulation Under Osmotic Stress in Lactobacillus rhamnosus ATCC 53103

Abstract: To determine whether osmotic pressure affects the translation efficiency of Lactobacillus rhamnosus, the ribosome profiling assay was performed to analyze the changes in translation efficiency in L. rhamnosus ATCC 53103. Under osmotic stress, differentially expressed genes (DEGs) involved in fatty acid biosynthesis and metabolism, ribosome, and purine metabolism pathways were co-regulated with consistent expression direction at translation and transcription levels. DEGs involved in the biosynthesis of phenylal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…High concentrations of sugars in marshmallows could trigger the osmosis process in probiotics, causing water loss from bacterial cells and affecting bacterial growth ( 52 ). Additionally, the survival of probiotics can be affected by the characteristics of the packaging material, such as thickness and gas permeability ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…High concentrations of sugars in marshmallows could trigger the osmosis process in probiotics, causing water loss from bacterial cells and affecting bacterial growth ( 52 ). Additionally, the survival of probiotics can be affected by the characteristics of the packaging material, such as thickness and gas permeability ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ubiquitous formation mechanism of persister cells depends on stress-induced inactivation of ribosomes, which ultimately leads to dormancy [ 20 ]. A previous study reported that Lactobacillus ribosomes are inactivated when exposed to stress [ 31 ]. This indicates that Lactobacillus is present in the persister cells because of the consequent inactivation of ribosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, mRNA level is only an approximate proxy for protein abundance, with a coefficient of determination in the range of ∼0.4–0.6 (Schwanhäusser et al , 2011 ; Wilhelm et al , 2014 ), suggesting that protein synthesis and decay rates are important layers of gene expression regulation. Translational control has been shown to play an important role in shaping the cellular proteome in bacteria (Li et al , 2014 ; Samatova et al , 2020 ; Tollerson & Ibba, 2020 ; Fan et al , 2021 ), eukaryotes (Leppek et al , 2018 ), human cells (Gingold et al , 2014 ; Jang et al , 2015 ), cancer cells (Gonzalez et al , 2014 ; Truitt & Ruggero, 2016 ; Robichaud et al , 2019 ), and virus‐infected cells (Stern‐Ginossar et al , 2019 ; Hernandez‐Alias et al , 2021 ). In Escherichia coli , proteins that are members of multiprotein complexes are produced in precise proportion to their stoichiometry mostly by tuning translation rates (Li et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%